The Incoming Paradigm Shift with Globalization and Clustering Approach - DÖNMEZ, CEM ÇAĞRI (ELSEVIER SCIENCE BV, 2016)
Clusters are a common reality in all economies and have traditionally been equated with cities. Transversely all European counties and towns there is a growing specialisation and focus or clustering of industries in response to increasing competition and outsourcing as a result of economic reorganisations and globalisation. Industry clusters comprise groups of firms that share regular suppliers, wholesalers and expertise and discover advantage in a specific geographic location. Alongside the transition from the mass manufacturing strategies to the adaptable manufacture techniques, on the basis theoretical work in the stream of clustering's have become the mutually reinforcing significant research field of the regional development hypotheses (Ocal and Ucar, 2011). The common applicability of this consummate, an agglomeration of firms which have been analysed within the framework of industrial localities in the past has now moved towards the clustering methodology has led to new discussions concerning the potential impacts of regional planning policies in the development of localised progress. The clustering seems by all accounts to be a dynamic significant component of the competition where the worldwide rivalries strengthen. While various clustering operating at this level prosper, the others vanish. Taking into account such bits of knowledge, the paper recommends a theoretical proposal, supported by practical evidence. And also, argues that clarify the issue of successful clustering into global consideration in different ways and Besides, this article tries to find an adequate response to the question whether the clustering's can be considered as a strategy of economic progress and regional development in the long term and It pays particular attention to the position of developing country. (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: Cluster; Competitiveness; Regional Development; Innovation and Productivity; STRATEGIES